Effects of water extracts of Artemisia annua L. on rumen immune and antioxidative indexes, fermentation parameters and microbials diversity in lambs - Gang, Gen; Gao, Ruiheng; Zhao, Huricha; Xu, Yuanqing; Xing, Yuanyuan; Jin, Xiao; Hong, Lei; Yan, Sumei; Shi, Binlin (Frontiers in Microbiology, 2024)
The present study investigated the effects of water extracts of Artemisia annua L. (WEAA) on rumen immune and antioxidative indexes, fermentation parameters and microbial diversity in lambs. A total of 32 3-month-old Dorper × Han female lambs having comparable body weights (24±0.09 kg) were selected and were randomly assigned to four treatments, with eight repetitions for each treatment. The basal diet, consisting of 45% concentrate and 55% forage, was solely provided to the control group. For the other treatment groups, the basal diet was supplemented with WEAA at dosages of 500, 1000, and 1500 mg/kg diet, respectively. Rumen tissue samples were collected for the analysis of immune and antioxidative parameters, as well as related gene expression. Rumen fluid samples were collected to assess rumen fermentation parameters on days 30 and 60 and to evaluate the microbiota on day 60. Results showed that WEAA supplementation linearly or quadratically increased the content of sIgA, IL-4, IL-2 and the gene expression level of MyD88, IκB-α, IL-4, COX-2, iNOS in rumen tissue (p < 0.05), as well as the bacteria negatively associated with IL-6 (g_ [Eubacterium] _cellulosolvens_group). Furthermore, the addition of WEAA linearly or quadratically increased rumen T-SOD,GSH-Px (p < 0.05) and the gene expression level of Nrf2, SOD2, GSH-Px, HO-1 (p < 0.05), and decreased the rumen concentration of malondialdehyde (MDA) and gene expression level of Keap1 (p < 0.05), as well as the bacteria positively associated with T-AOC, T-SOD and GSH-Px (g_Lachnospiraceae_NK3A20_group, g_Saccharofermentans, g__Marvinbryantia, g_unclassified_f_Eggerthellaceae). The supplementation of WEAA caused the concentration of microprotein (MCP), total volatile fatty acids (TVFA), propionate to increase either linearly or quadratically, while reducing the concentration of NH3-N and the acetate/propionate ratio (A:P) in rumen fluid (p < 0.05). The addition of WEAA linearly or quadratically increased the abundance of Actinobacteriota, Cyanobacteria and Lachnospiraceae_NK3A20_group (p < 0.10), and g__Lachnospiraceae_NK3A20_group, g_Saccharofermentans, g_Marvinbryantia, g_Bifidobacterium were significantly abundant as specific microflora in the 1000 mg/kg WEAA supplementation group. In conclusion, dietary inclusion of 1000 mg/kg WEAA improved the rumen immune function, antioxidant status, rumen fermentation, and composition of rumen microbes in lambs.